2015
DOI: 10.1121/1.4904528
|View full text |Cite
|
Sign up to set email alerts
|

A survey of acoustic conditions and noise levels in secondary school classrooms in England

Abstract: An acoustic survey of secondary schools in England has been undertaken. Room acoustic parameters and background noise levels were measured in 185 unoccupied spaces in 13 schools to provide information on the typical acoustic environment of secondary schools. The unoccupied acoustic and noise data were correlated with various physical characteristics of the spaces. Room height and the amount of glazing were related to the unoccupied reverberation time and therefore need to be controlled to reduce reverberation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 21 publications
3
56
0
4
Order By: Relevance
“…Indoor noise and echo level evidenced an inverse relation between acoustic factor and academic performance, which confirms previous research [10][11][12][13][14]. However, its influence is lower in the practice room, where students work in small groups and communication does not need to reach a big audience.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indoor noise and echo level evidenced an inverse relation between acoustic factor and academic performance, which confirms previous research [10][11][12][13][14]. However, its influence is lower in the practice room, where students work in small groups and communication does not need to reach a big audience.…”
Section: Discussionsupporting
confidence: 87%
“…An auditory feature, such as background music, has proved to promote collaborative behaviour and support good humour [9]. Also, noise, reverberation and distracting sounds interfere with communication, which may lead students to low information processing efficiency [10][11][12][13][14]. carried out with highly motivated students.…”
Section: Introductionmentioning
confidence: 99%
“…providing an estimate of LAeq, [8][9][10][11][12][13][14][15][16][17] h with a standard deviation of the error of ±0.5 dB and a coefficient of determination R 2 = 0.993 as shown in Figure 2c, where the prediction bands at the 95% confidence level are also plotted (blue lines). The median value of the error is 0.0 dB and for 98.5% of the observations in the dataset, the error is within the range ±1.5 dB.…”
Section: Noise Level At School Facades: Correlation Between Lden Daymentioning
confidence: 99%
“…Since the 1970s, many researchers have analyzed how chronic noise exposure affects the cognitive processes [1][2][3][4][5][6][7][8][9][10][11][12]. Researchers found that the disturbance caused by occasional noisy events such as overflying aircraft, pass-by trains, heavy trucks, motorcycles, street sweepers, or sirens may affect adults and children disproportionately compared to their contribution to the overall noise environment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the acoustic characteristics in classrooms for students with hearing impairment is of extreme importance, once in the school environment, the noise is not only an annoyance but also interferes with the performance of teaching activities (1,2) . The noise and its effects on the human organism have been arousing interest in various areas related to education and health (3) .…”
Section: Introductionmentioning
confidence: 99%